2017
DOI: 10.15415/jnp.2017.51017
|View full text |Cite
|
Sign up to set email alerts
|

Study of L-Glutamic Acid in Solid State for its Possible Use as a Gamma Dosimeter at Different Temperatures (77, 195 and 295 K)

Abstract: Research using hybrid pixel detectors in medical physics is on the rise. Timepix detectors have arrays of 256 × 256 pixels with a resolution of 55 µm. Here, and by using Timepix counts instead of Hounsfield units, we present a calibration curve of a Timepix detector analog to those used for CT calibration. Experimentation consisted of the characterization of electron density in 10 different kinds of tissue equivalent samples from a CIRS 062M phantom (lung, 3 kinds of bones, fat, breast, muscle, water and air).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…It has also been reported that aspartate and glutamate are among the amino acids most resistant to ionizing radiation, while cysteine is among the least resistant, 92 as well as aspartate and glutamate residues involved in the formation of salt bridges are less affected, and may even be completely resistant to radiation damage 37 . Remarkably, glutamate has been proposed as a dosimeter of γ‐radiation 93 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that aspartate and glutamate are among the amino acids most resistant to ionizing radiation, while cysteine is among the least resistant, 92 as well as aspartate and glutamate residues involved in the formation of salt bridges are less affected, and may even be completely resistant to radiation damage 37 . Remarkably, glutamate has been proposed as a dosimeter of γ‐radiation 93 …”
Section: Resultsmentioning
confidence: 99%
“…37 Remarkably, glutamate has been proposed as a dosimeter of γ-radiation. 93 The structural study of the PCNA Tg by X-ray crystallography, both global damage and specific damage, reveals that it is a protein with the intrinsic ability to resist high levels of ionizing radiation. Since all proteins have mainly the same repertoire of amino acids and interactions, it seems clear that their properties depend on a complex balance of these factors, 20,73,74 and it has also been suggested that the radioresistance shown by hyperthermophilic archaea could be a consequence of the adaptation of life at high temperatures.…”
Section: Biological Scopementioning
confidence: 99%